Relative and Interraction Effects of Errors in Physics Practical - Thomas, Owolabi Olabode (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> The importance of physics in human endeavour cannot be glossed over, for it places a vital role and essential part of all human endeavour, especially in science and technology. The study was designed to see the relative and interraction effects of errors in physics practical in Nigeria Secondary Schools. A Quasi experimental design of the three group pre-test, post-test, control design was employed. The sample for the study consisted of sixty (60) students from three selected secondary schools in Nigeria. Equal male and female students were selected using stratified random sampling technique. Physics Practical Questions (PPQ) were validated and used before and after treatment in the groups. The findings revealed that when students are exposed to the idea of errors in practical physics, the degree of accuracy will increase and therefore enhance their performance in the subject. Physics and related courses had been recommended for both male and female students in secondary schools, since sex is not the major issue in physics practical works. If the students are taught how to get accurate results and errors are minimised in physics practical, this will enhance good performance in the subject. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->